Profile of Type 2 Diabetes Mellitus Patients and Its Implications for Health Promotion Strategies at Sanden Public Health Centre (2022-2024) - Novi Wijayanti; Elvina Prisila; Zainul Arifin; Dewi Yuniasih; Febrianti Putri Nurulita; Widya Rahmawati (UMSU, 2025)
Abstract: Type 2 Diabetes Mellitus (T2DM) remains a significant public health challenge globally, particularly in low- and middle-income countries such as Indonesia. Understanding the sociodemographic and clinical profiles of diabetic patients is essential for designing targeted interventions and improving disease outcomes. This descriptive study aimed to analyze the characteristics of T2DM patients registered at the Sanden Primary Health Center, Bantul Regency, from 2022 to 2024. Data were collected from the chronic disease program (PROLANIS) register, encompassing patient identity, blood sugar levels, and clinical complications. Among 86 patients, 79.07% were female, and the most prevalent age group was 56–65 years (44.19%). Some patients experienced complications, including peripheral circulatory disorders (3.35%) and neurological complications (1.97%).These findings underscore the need for strengthened patient education, lifestyle modification support, and routine clinical monitoring to manage T2DM effectively at the primary care level. Additionally, community-based health promotion strategies, utilizing simplified communication, culturally relevant content, and visual media, are urgently needed to reach vulnerable groups, especially elderly women with limited educational attainment.Keywords: Type 2 Diabetes Mellitus, Patient Profile, Primary Health Care, PROLANIS, Indonesia, Health Promotion, Complications